PENDAMPINGAN PENGELOLAAN JURNAL IJOBEC (INTERNASIONAL JOURNAL OF ENGLISH BUSINESS ENGLISH AND COMMUNICATION) - Sakkir, Geminastiti; Muhayyang, Maemuna; Amin, Fatimah Hidayahni; Dollah, Syarifuddin; Noni, Nurdin; Umar, Nur Fadhilah (PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 2023)
Kegiatan pendampingan ini bertujuan untuk memberikan pengetahuan, pemahaman dan keterampilan dasar bagi para staf editor pengelola jurnal IJOBEC tentang tampilan dan sistem pengelolaan jurnal yang baik. Dalam kegiatan ini, para dosen memberikan presentasi dan diskusi tentang berbagai hal yang diperlukan jika ingin mengelola jurnal, meliputi: tampilan menu jurnal di web, cara mengedit tampilan menu jurnal, dan cara mengisi artikel pada web jurnal. Kegiatan ini diikuti oleh para dosen pengabdi, kaprodi BEC, dan dua orang staff pengelola jurnal IJOBEC. Hasil dari kegiatan pendampingan ini menunjukkan bahwa para staf pengelola jurnal IJOBEC sangat terbantu dalam merancang tampilan jurnal di web, mengedit tampilan menu yang tersedia dan mengetahui cara memasukkan artikel di jurnal tersebut. Mereka sangat antusias dalam mengikuti kegiatan ini dan mengakui bahwa kegiatan ini sangat bermanfaat bagi mereka. Para staf pengelola jurnal IJOBEC dan kaprodi BEC juga berharap dan menyarankan agar adanya kegiatan lanjutan sehingga jurnal tersebut dapat menerbitkan artikel tepat waktu tiap edisi dan dapat menjadi jurnal yang terakreditasi. This assistance activity aims to provide basic knowledge, understanding, and skills for editorial staff managing the IJOBEC journal regarding the appearance and good journal management system. In this activity, the lecturer gave a presentation. They discussed various things that are needed if you want to manage a journal, including: how to display the journal menu on the web, how to edit the appearance of the journal menu, and how to fill in articles on the web journal. This activity was attended by service lecturers, heads of the BEC study programs, and two management staff of the IJOBEC journal. The results of this mentoring activity show that the managing staff of the IJOBEC journal is greatly assisted in designing the journal's appearance on the web, editing the available menu views, and knowing how to enter articles into the journal. They were very enthusiastic about participating in this activity and admitted that this activity was very useful for them. The managing staff of the IJOBEC journal and the head of the BEC study program also hope and suggest that further activities be carried out so that the journal can publish articles on time for each edition and can become an accredited journal.